Employment and decentralization in Peru in the XXI century - Iguíñiz Echeverría, Javier (1994)
In this time of growing globalization and the power of science in economic activity and, in the case of Peru, in the midst of a long process of "costeñización" of the population and of production and services, is it possible to think of a strategy of long-term development that it has in the mountains, and should we add the jungle, one of the leading places? In this work we intend to show, to the degree to which we have advanced in the answer, that this is possible if the place occupied by the sierra in the national economy changes radically.